Agricultural productivity and policies in Sub-Saharan Africa - Yu, Bingxin; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2011)
We analyze the evolution of Sub-Saharan Africa's (SSA's) agricultural total factor productivity (TFP) over the past 45 years, looking for evidence of recent changes in growth patterns using an improved nonparametric Malmquist index. Our TFP estimates show a remarkable recovery in the performance of SSA's agriculture between 1984 and 2006 after a long period of poor performance and decline. That recovery is the consequence of improved efficiency in production, resulting from changes in the output structure and an adjustment in the use of inputs. Policy interventions, including fiscal, trade, and sector-specific policies, appear to have played an important role in improving agricultural performance. Despite the improved agricultural performance, economies in SSA face serious challenges to sustain growth. Among these are the small contribution of technological change to TFP growth in the past, the large tax burden imposed by remaining distortions, and the challenge of population growth.